Antecedents and Consequences of Career Decision-Making Self-efficacy in High School Students: A Scoping Review - Agustinus Budi Nugroho; Dian Ratna Sawitri (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
One of the developmental tasks of adolescence is making career decisions. High school students are at the stage of making career decisions. Many high school students are still unsure and unable to make career decisions. Career Decision Making Self-efficacy based on Bandura's (1986) Social Cognition Theory provides an understanding of how self-efficacy plays a role in making career decisions. This article aims to show the variables that are the antecedents and consequences of career decision self-efficacy. For this reason, the method used is a Scoping Review to map the antecedents and consequences of Career Decision Making Self-efficacy. PRISMA is used to assist the selection process of articles to be studied. The scope and review were conducted using the PRISMA approach and three databases: Springer Link, Scopus, and GARUDA. The search and selection process was finalized after determining the included and excluded criteria. The search and selection process resulted in 14 empirical articles published in 2014-2024. A study of 14 articles found nine CDMSE antecedents and four CDMSE consequences. The results of this literature study can be used by parents, counselors and guidance and counseling teachers to assit high school and vocational school students in making career decisions. In addition, the results of this study can be used as a basis for further CDMSE research.